Compulsory Insurance Against Damage Caused by Natural Disasters - Ann-Kristin Becker; Christoph Oslislo (Wirtschaftsdienst)
Abstract Like the floods of 2002 and 2013, the consequences of the flood in July 2021 have dramatically demonstrated the need for comprehensive climate adaptation measures in Germany. In this context, the government has for the third time commissioned a working group to examine an insurance obligation against natural hazards. While the basic arguments in the debate are not new, there are still several open questions on the central design and implementation details. We draw attention to the key economic trade-offs in this debate and argue that the frequent criticisms of compulsory insurance are based on specific design assumptions and therefore do not serve as general arguments against an insurance obligation.